Combined method of whole mount and block‐face imaging: Acquisition of 3D data of gene expression pattern from conventional in situ hybridization. (13th December 2022) - Sutrisno, Aldy Anindyawan; Katano, Wataru; Kawamura, Hayata; Tajika, Yuki; Koshiba‐Takeuchi, Kazuko
Abstract: Visualization of spatiotemporal expression of a gene of interest is a fundamental technique for analyzing the involvements of genes in organ development. In situ hybridization (ISH) is one of the most popular methods for visualizing gene expression. When conventional ISH is performed on sections or whole‐mount specimens, the gene expression pattern is represented in 2‐dimensional (2D) microscopic images or in the surface view of the specimen. To obtain 3‐dimensional (3D) data of gene expression from conventional ISH, the "serial section method" has traditionally been employed. However, this method requires an extensive amount of time and labor because it requires researchers to collect a tremendous number of sections, label all sections by ISH, and image them before 3D reconstruction. Here, we proposed a rapid and low‐cost 3D imaging method that can create 3D gene expression patterns from conventional ISH‐labeled specimens. Our method consists of a combination of whole‐mount ISH and Correlative Microscopy and Blockface imaging (CoMBI). The whole‐mount ISH‐labeled specimens were sliced using a microtome or cryostat, and all block‐faces were imaged and used to reconstruct 3D images by CoMBI. The 3D data acquired using our method showed sufficient quality to analyze the morphology and gene expression patterns in the developing mouse heart. In addition, 2D microscopic images of the sections can be obtained when needed. Correlating 2D microscopic images and 3D data can help annotate gene expression patterns and understand the anatomy of developing organs. These results indicated that our method can be useful in the field of developmental biology. Abstract : We proposed a rapid and low‐cost 3D imaging method that can create 3D gene expression patterns from conventional in situ hybridization specimens. This method is useful for spatiotemporal analyses of the expression patterns of genes of interest and morphological changes during organ development.